PEMBUKTIAN SUMPAH DI PERADILAN AGAMA - Hernowo Bayu Wicaksono, Aqsha Surgana (GEMA, 2015)
Verification is a process in the court proceedings , both criminal and civil procedure . Verification is a critical phase in the proceedings in court , the person who proves not necessarily win but those who can not prove for sure lose . In the event legal religious court also found the evidence in the proceedings in the court , where the proof is the same as in the civil law . In the most important evidence is a tool - a tool that is used or presented evidence at trial to prove the process . Any of that evidence is evidence oath , which is also known in the religious court oath about the evidence . Oath is an utterance of the truth about a matter that the person who swore the oath directly responsible to the Almighty God who is responsible for the judicial means Allah SWT . Oath itself is no different - varying in religious courts where there are also unknown oath in civil court for example liin oath . With this oath evidence expected in the process of proving faster in finding a bright spot who is right and who is wrong , rather than to be mocked just to earn the victory . So with this oath in a court case is expected to trade quickly resolved in the interests - fair .Therefore , in this paper we will describe and discuss the evidence sworn in court proceedings in accordance with the religion of al quran , al Hadith and regulations - regulations that relate to the oath of proof so that it can provide benefits for the settlement of disputes in religious courts in in particular